Social and Ecological Factors Affect Long-Term Resilience of Voyaging Canoes in Pre-contact Eastern Polynesia: A Multiproxy Approach From the ArchaeoEcology Project - Kahn, Jennifer G.; Buffington, Abigail; Escue, Claudia; Crabtree, Stefani A. (Frontiers in Ecology and Evolution, 2022)
While all communities who initially settled Eastern Polynesia archipelagoes must have done so with large double-hulled canoes, their use was absent in some societies by the time of European contact. We question why some Eastern Polynesian societies retained the use of large ocean-going canoes, while others did not. For high island archipelagoes like the Society Islands, sources document how large double-hulled canoes facilitated and supported elite intra-archipelago voyaging, warfare, and exchange with near and remote hinterlands up until European contact in the mid-18th century. While smaller canoes were used by commoners on a daily basis for subsistence fishing and island-wide transport, larger ocean-going canoes were strictly the purview of high-ranking elites. Our human-centered interaction network models help us to identify how social processes put constraints on the manufacture and continued use of large ocean-going vaʻa in Eastern Polynesian contexts. We deploy such data to outline steps in the production, use, and re-use of canoes. We employ network science to better understand the relationships between animal and plant species used by the Māʻohi in canoe manufacture, quantifying the number of resources used, the number of social personae involved, and the amount of labor/energy involved in their manufacture. Finally, we use Moʻorea settlement pattern data, as well as landscape and elevation data, to visually model the extent to which local ecologies or habitats constrained access to long-lived hard wood trees, key raw materials in the construction of ocean-going vessels. We consider the additional variables of soil pH and tree regrowth rates in our modeling of the ecological limits of preferred vaʻa species. We then query differential patterns of continued use of ocean-going vessels in two Eastern Polynesian archipelagoes: the Gambier archipelago and the Society Islands. Utilizing these multiple sources of data, we return to the age-old question of what role social processes and natural processes played in the resiliency of the socio-political systems of Polynesian chiefdoms.